(untitled) (Nordic Journal of Practical Theology, 2021)
How do bishops and deans describe their authority in leading ministers between ecclesial oversight and employer` s responsibility? The question has become topical and controversial due to an upcoming church reform, with a major report suggesting that the latter should be taken care of by lay managers. I have interviewed bishops and deans about strategic leadership and analysed their answers according to Tian Sørhaug` s theory of management within mixed knowledge regimes, including hierarchy, collegium and network. Pastoral calling, ecclesial commitment and collegial discussions on theolgy were emphasised by the respondents as key ressources for church leadership, combining " oversight" with "employer/employee" relations. The article analyses how the two forms of leadership support each other today, but might collapse if the direct link between bishops, deans and parish ministers is broken.